2009
DOI: 10.1097/qad.0b013e328325d115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulmonary tuberculosis on mortality in patients receiving HAART

Abstract: The increase in death that we observed among individuals with PTB at the time of HAART initiation appears not to be due to the to the presence of PTB, but instead to confounding factors such as low CD4 cell count, low BMI, and WHO stage IV disease. These results further demonstrate that initiation of HAART soon after initiation of PTB treatment is not likely to put patients at higher risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 28 publications
7
57
2
Order By: Relevance
“…Even if the overall survival rate is lower for PLWHs with TB co-infection at the time of ART initiation, the presence of TB co infection was not found to increase the risk of death after accounting for the effect of other confounding factors in Cox-regression model. Other published studies in Taiwan [3], Malawi [17] and South Africa [18] have also shown similar findings.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Even if the overall survival rate is lower for PLWHs with TB co-infection at the time of ART initiation, the presence of TB co infection was not found to increase the risk of death after accounting for the effect of other confounding factors in Cox-regression model. Other published studies in Taiwan [3], Malawi [17] and South Africa [18] have also shown similar findings.…”
Section: Discussionsupporting
confidence: 77%
“…This finding is comparable with study in India [15], Taiwan [13] and South Africa [18]. The lower survival rate in cohort with TB observed in this study could be due to the fact that TB patients are more likely to have severe immunosuppression (low CD4 counts), low BMI, and anemia when ART initiated than others.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations